Transforming Participation into Institutional Power Youth Leadership in Sports Governance A Scoping Review - Mary Jida; SM Farooque; Sumit Deori (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Youth participation in sport is widespread, yet their representation in formal governance structures remains limited. Although inclusive and democratic governance is increasingly emphasized, it is unclear whether youth leadership translates into meaningful institutional power within sport organizations. This scoping review maps existing scholarship on youth leadership in sports governance, examines how youth roles are conceptualized, and evaluates the extent of decision-making authority afforded to young leaders across governance levels. Methods: Following the Wong framework and reported in line with PRISMA-ScR guidelines, a comprehensive search was conducted across Scopus, Web of Science, SPORTDiscus, ERIC, and Google Scholar. Studies addressing youth leadership or representation in sport governance were included. Records were screened using predefined criteria, and data were charted to capture governance levels, leadership roles, authority structures, and reported barriers or outcomes. Findings were synthesized thematically. Result: Youth leadership is increasingly visible through advisory boards, athlete commissions, and youth councils; however, substantive authority such as voting rights and strategic influence remains limited. Key barriers include age-based legitimacy bias, hierarchical governance cultures, short-term appointments, and limited mentorship pathways. Where formal authority and governance training exist, youth leaders contribute to improved legitimacy and policy responsiveness. Conclusion: Youth leadership in sports governance remains positioned between symbolic inclusion and genuine power-sharing. Advancing toward institutional authority requires structural reforms, including formal representation, voting rights, and intergenerational governance models to strengthen democratic legitimacy and long-term sustainability.